Pengarusutamaan Ekopedagogik Pada Keluarga Petani di Desa Bulutellue Kecamatan Bulupoddo Kabupaten Sinjai - Abdul Rahman; Andi O Tenriawaru; Ahmadin Ahmadin (UIN Fatmawati Sukarno Bengkulu, 2022)
has become a reality that the earth and all the resources contained in it have been exploited to fulfill material interests and pursue economic income. As a result, the earth began to experience an imbalance marked by the emergence of various natural disasters. This reality encourages the educational environment, be it schools, families and communities to try again to maintain the balance of the earth and environmental sustainability through an ecopedagogic approach. On this basis, this research seeks to elaborate in depth the efforts of farmers in Bulutellue Village in mainstreaming ecopedagogic activities. This research was conducted using a qualitative approach through ethnographic methods. The results showed that the farming community in Bulutellue Village as part of the community that still cares about environmental sustainability tries to apply ecopedagogy to their children in their daily lives, both in the household environment and on agricultural land. Activities that have an ecopedagogic nuance can be seen when children are involved in cleaning the yard and yard of the house, making compost from kitchen waste and livestock manure to reducing consumption of packaged food and drinks.This practice has proven to be effective because children from farming families can directly apply the knowledge they get at school.